Augmented Reality Markerless Implementation Method in Benign Education Application for Prostatic Mobile-Based Hyperplasia (BPH) - Muhammad Fari Abiyyudhiya; Neny Rosmawarni; Hamonangan Kinantan Prabu (Research Synergy Foundation, 2026)
Technological developments in recent years have brought significant changes in education, particularly through the integration of Information and Communication Technology (ICT). ICT enables broader and more flexible access to learning resources through distance learning, educational applications, and digital platforms. One notable innovation is Augmented Reality (AR), which integrates two-dimensional (2D) and three-dimensional (3D) virtual objects into real-world environments in real time, providing more interactive and concrete learning experiences. This study aims to develop a mobile-based educational application using markerless Augmented Reality to improve the general population's understanding of Benign Prostatic Hyperplasia (BPH). This common health condition remains poorly understood. The research methodology adopts the Multimedia Development Life Cycle (MDLC), which consists of concept, design, material collection, assembly, testing, and distribution stages. The application was developed using Unity and Vuforia SDK and implemented on mobile devices. The findings show that the developed application functions properly, as demonstrated by black-box testing and markerless distance testing. Questionnaire and knowledge test results indicate that users' understanding of BPH improved after using the application. Users also provided positive feedback regarding usability, visual quality, and the effectiveness of AR-based learning. In conclusion, the proposed markerless AR educational application is an effective interactive learning medium for increasing public awareness, supporting early understanding, and encouraging timely treatment of Benign Prostatic Hyperplasia.